The Relationship of Playing Ball Bekel Method on Improving Cognitive Development in Early Childhood - Yuyun Rahayu Uhar; Ima Sukmawati; Heni Marliany; Resna Litasari; Mega Sri Utami; Iim Imas Masru'ah (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2023)
Background: children must remember information in the learning process in class, because it still often comes from the teacher, and this causes children to be lazy in thinking skills and when solving problems less than ideal. Teachers rarely use interesting media such as playing methods that make children not interested in following the learning process.Purpose: this study aims to determine the relationship of the bekel ball playing method on increasing cognitive development in early childhood.Methods: the research method used is analytic method with cross sectional approach. The population used in this study were all 41 children of Dewi Sartika 3 Kindergarten. The sampling technique used was a accidental sampling method of 30 people. Data were analyzed using the chi-square computerized technique and the research instruments used observation sheets and bekel balls .Results: the results showed that there was an effect of the bekel ball playing method on increasing cognitive development in early childhood at Dewi Sartika 3 Kindergarten because the p value < (0.02 < 0.05).Conclusion: the conclusion in this study is that there is an relationship of the bekel ball playing method on increasing cognitive development in early childhood at Dewi Sartika 3 Kindergarten.